SELF-REGULATED LEARNING STRATEGY DEVELOPMENT ON ENHANCING STUDENTS READING COMPREHENSION SKILLS - Moh. Rif'attullah; Putra, Fahry Rizaldy (Institut of Shanti Bhuana, 2023)
This conceptual paper explores the importance of self-regulated learning strategy development in enhancing students' reading comprehension skills. It presents an overview of empirical research conducted in this area, emphasizing the impact of metacognitive self-regulated strategies on students' comprehension, engagement, and overall academic success. The paper discusses the Self-Regulated Strategy Development (SRSD) model as a framework for implementing self-regulated learning strategies in reading instruction. The six stages of SRSD, including developing background knowledge, discussing, and modeling the strategy, memorizing it, supporting its use, and establishing independent practice, are outlined as a comprehensive approach to fostering metacognitive awareness and self-regulation in reading. This paper underscores the importance of incorporating self-regulated learning strategies into reading comprehension to empower students as independent, metacognitive readers. By equipping students with cognitive and metacognitive tools, educators can foster a lifelong love for reading and enhance students' comprehension abilities, leading to academic success and continued growth as self-regulated learners.